2013
DOI: 10.1002/bies.201200169
|View full text |Cite
|
Sign up to set email alerts
|

How epigenetic mutations can affect genetic evolution: Model and mechanism

Abstract: We hypothesize that heritable epigenetic changes can affect rates of fitness increase as well as patterns of genotypic and phenotypic change during adaptation. In particular, we suggest that when natural selection acts on pure epigenetic variation in addition to genetic variation, populations adapt faster, and adaptive phenotypes can arise before any genetic changes. This may make it difficult to reconcile the timing of adaptive events detected using conventional population genetics tools based on DNA sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
271
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(292 citation statements)
references
References 49 publications
10
271
0
1
Order By: Relevance
“…Pure epigenetic variation may also help populations respond to environmental change. A recent theoretical study has suggested that when selection acts on pure epigenetic variation as opposed to obligatory epigenetic variation, adaptive phenotypes can occur before genotypic change due to the higher rate of epimutation permitting faster exploration of the fitness landscape (Klironomos et al, 2013). However, none of the empirical work to date has addressed pure epigenetic variation in animals, possibly due to the difficulty of establishing genetically identical populations.…”
Section: The Evolutionary Potential Of Epigenetic Variationmentioning
confidence: 99%
“…Pure epigenetic variation may also help populations respond to environmental change. A recent theoretical study has suggested that when selection acts on pure epigenetic variation as opposed to obligatory epigenetic variation, adaptive phenotypes can occur before genotypic change due to the higher rate of epimutation permitting faster exploration of the fitness landscape (Klironomos et al, 2013). However, none of the empirical work to date has addressed pure epigenetic variation in animals, possibly due to the difficulty of establishing genetically identical populations.…”
Section: The Evolutionary Potential Of Epigenetic Variationmentioning
confidence: 99%
“…This may be followed by compensatory mutations that increase fitness by reversing the effect of the initial mutation on traits where change was not adaptive (46)(47)(48). Second, heritable epigenetic mutations or transgenerational plasticity can contribute to early adaptation (7) but eventually be replaced by genetic mutations (49)(50)(51)(52). Understanding how trait reversion is linked to adaptation presents an opportunity to improve our predictions of functional trait values in primary producers in aquatic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining adults at elevated temperature during gonad development and maturation can affect subsequent generations, regardless of future temperatures, through epigenetic effects, which can speed up the rate at which genetic evolution can occur (Klironomos et al, 2013). Without being able to follow single parent crosses it is not possible to assess the heritability of thermal acclimation from the current study.…”
Section: Discussionmentioning
confidence: 99%